2013
DOI: 10.1186/1756-0500-6-531
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of potentially pathogenic nontuberculous mycobacteria in Mexican household potable water: a pilot study

Abstract: BackgroundNontuberculous mycobacteria (NTM) are environmental opportunistic pathogens found in natural and human-engineered waters, including drinking water distribution systems and household plumbing. This pilot study examined the frequency of occurrence of NTM in household potable water samples in Mexico City. Potable water samples were collected from the “main house faucet” and kitchen faucet. The presence of aerobic-mesophilic bacteria (AMB), total coliforms (TC), fecal coliforms (FC) and NTM species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Indeed, M. porcinum has mainly been reported in water supplies in tropical or subtropical areas in the USA (22,23), Iran (24), Brazil (25) and Mexico (26). We report M. porcinum isolates identified in three patients with M. porcinum lung infection according to the ATS criteria (13), which is consistent with other cases reported previously, particularly in subtropical areas such as Texas and Florida, where clonal dissemination was ob- served, particularly through water systems (22,27).…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, M. porcinum has mainly been reported in water supplies in tropical or subtropical areas in the USA (22,23), Iran (24), Brazil (25) and Mexico (26). We report M. porcinum isolates identified in three patients with M. porcinum lung infection according to the ATS criteria (13), which is consistent with other cases reported previously, particularly in subtropical areas such as Texas and Florida, where clonal dissemination was ob- served, particularly through water systems (22,27).…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we combined conventional and molecular methods and detected and identified NTM in 7 RTE-salads and 12 RTE-sprouts. All NTM identified in this study have also been found in Mexican water samples [ 53 ] and in water samples from other countries [ 21 , 54 ]. Therefore, it is possible that water may be the original source of NTM transmission to vegetables (used in the salads) or sprouts while growing or during harvesting, washing, slicing, soaking, packaging, and preparation.…”
Section: Discussionmentioning
confidence: 56%
“…A total of 13 dams were entitled for the purpose of this study, with almost 520 isolates being collected (between 20 and 30 July of 2013) from multiple environmental resources such as sands, clay, wet stones, and decayed vegetation. Furthermore, a large proportion (79%) of collected isolates yielded positive results for NTM, which is more than that reported elsewhere [53, 54]. In addition, 145 isolates were carefully selected and subjected to species identification process by Alqumber (2014).…”
Section: Environmental Diversity Of Ntmmentioning
confidence: 99%